The Effect of Using KBS1B IEC Videos on Ease, Knowledge, and Attitudes of One-Month Injectable Contraceptive Acceptors - Novtarina Sitanggang; Siti Sugih; Herri S. Sastramihardja; Yanti Herawati; Teni Nurlatifah (GLOBAL HEALTH SCIENCE GROUP, 2025)
According to the World Health Organization (WHO) in 2022, the use of family planning in Asia has increased. In Indonesia, the coverage of contraceptive methods within family planning programs is substantial. The role of family planning programs has a significant impact on both women's and men's reproductive health. This study aims to assess the effectiveness of video media in influencing the convenience, knowledge, and attitudes of one-month injectable contraceptive acceptors at PMB I in Sumedang Regency. The study used research (quasi experimental research) with pre and post test design with control group. This research was conducted in July - August 2024 at PMB I Sumedang Regency. The sample in this study consisted of mothers who had attended more than two follow-up visits for 1-month injectable contraceptives. The sampling technique uses total sampling, with a total of 60 respondents, divided between intervention and control groups, with pretest and posttest conducted. An Independent Sample t-test was used for data analysis. The respondents were predominantly between 31-45 years old (63.3%). In both the intervention and control groups, 50% of respondents were aged 30 years or younger. The majority of respondents had an education level of elementary, middle, or high school, and most were unemployed or homemakers. The normality test results were found to be insignificant, prompting the use of non-parametric analysis. The results showed that respondents' knowledge about 1-month family planning (p=0.000), attitudes (p=0.095), and ease of use (p=0.000) were better in the intervention group using video compared to the control group using leaflets. The conclusion of this study is that video media proved more effective in improving user convenience, knowledge, and attitudes compared to leaflets. Thus, video is a more readily accepted form of media in the community.